ESTUDO DA SUBSTITUIÇÃO DE CIMENTO PORTLAND PELO FINO DE BRITAGEM EM ARGAMASSA AUTO-ADENSÁVEL - Fortunato, Morgana; Martins, Ben-hur Raíra; Casali, Juliana Machado; Collodetti, Giovana; Betioli, Andrea Murillo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The use of self-compacting mortars provides a more efficient production process. However, the high consumption of cement raises the cost and can lead to cracking of the subfloor. In order to reduce de consumption of cement, there is the possibility of using alternatives materials as stone dust and others residues that fulfill the function of binder and can preserve or even improve the properties of the final product. The stone dust is an interesting alternative for the substitution of the cement. It is a residue from the aggregate´s production. In the present research, four self-compacting mortars were produced. One without cement substitution assuming reference function, and the others replacing in 5%, 10% and 20% the volume of cement by stone dust. In the fresh state, the mortars with 5% and 10% substitution obtained the necessary fluidity to become self-compacting mortar. As for the mechanical performance, there was a small reduction in flexural tensile strengths and compressive strength, due to the increasing in the water/cement ratio and the incorporate air content. Despite this reduction, the lower compressive strength values are still above the minimum limit for all mortars tested.